Manajemen Satuan Pendidikan Tinggi - Wahyani, Sri; Susilowaty, Susilowaty; Astuti, Puji; Suwandari, Lilis (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Higher education plays a strategic role in producing superior human resources capable of facing global challenges. The success of higher education delivery is largely determined by the effectiveness of educational unit management, encompassing planning, organizing, directing, and controlling. This research, conducted using a literature review method, aimed to examine the key dimensions of higher education management, such as learning management, human resource management, financing management, and facilities and infrastructure management. The results of the study indicate that these four managerial functions are interconnected and must be synergistically integrated to achieve efficient and high-quality higher education governance. The analysis chart shows that the planning function has the highest contribution to institutional effectiveness, followed by directing, controlling, and organizing. Furthermore, the use of Management Information Systems (MIS) is a crucial instrument in integrating these functions and supporting data-driven decision-making. Therefore, an adaptive, technology-based, and responsive managerial approach to national policy is needed to drive sustainable higher education transformation. Keywords: Higher Education, Educational Management, Learning Management, Facilities and Infrastructure, Human Resource Management, Financing Management.